Efektivitas Penerapan Metode An Nahdliyah Dalam Pembelajaran Al-Qur’an Tpq Sabilil Huda Desa Bedingin Sambit Ponorogo - Siti Kalimatur Rosidah; Rinesti Witasari (https://ejournal.insuriponorogo.ac.id/, 2023)
The article aims to find out how effective children are in learning the qur 'an by using an nahdliyah's method to increase the motivation for learning the Qur’an of children in TPQ sabilil huda village bedwant district sambit ponorogo. This article is set in the background by a common phenomenon today of declining or lack of motivation for children to study the qur’an. Whereas study or science is a duty to every Muslim from birth to the end of his or her life. Most communities are indifferent to religious education primarily in the quran reading. Looking at this problem surely we need to figure out how to prevent children from getting bored and excited about learning the qur 'an, this research is a sort of descriptive qualitative research using methods of interviews and documenting. Research shows that an nahdliyah's method was effectively implemented on TPQ sabilil huda village bed, as is shown by the increased ability to read the qur’an and the spirit of the santri on TPQ sabilil huda.